2008
DOI: 10.3366/e0260954108000119
|View full text |Cite
|
Sign up to set email alerts
|

Les figures des plantes et animaux d'usage en medecine, a rare work published by F. A. P. de Garsault in 1764

Abstract: Between 1764 and 1767 the artist and naturalist F. A. P. de Garsault published several editions of the five-volume work Les figures des plantes et animaux d'usage en medecine, in which hundreds of plants (four volumes) and animals (one volume) were figured and presented with French and Latin names. A strict absence of polynominal Latin names in the animal volume is a surprising contrast to the botanical volumes where many polynominal names were used. Although several Latin zoological names entered taxonomy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…It is here suggested that, if such a generic nomen is rediscovered after 1999, its nucleospecies could be fixed only by subsequent explicit designation, not by subsequent monophory. Such cases are rare nowadays, but still may occur, are well illustrated with the recent rediscovery by Welter-Schultes et al (2008) of Garsault's (1764) work. In their treatment of the amphibian and reptile nomina in this work, Dubois & Bour (2010a) explicitly designated nucleospecies for the genera, without taking into account the fact that, in a few cases, Welter-Schultes & Klug (2009) had mentioned a single nominal species as belonging to this genus-while clearly stating that they did not designate nucleospecies in their paper.…”
Section: Modes Of Designation Of Onomatophoresmentioning
confidence: 98%
“…It is here suggested that, if such a generic nomen is rediscovered after 1999, its nucleospecies could be fixed only by subsequent explicit designation, not by subsequent monophory. Such cases are rare nowadays, but still may occur, are well illustrated with the recent rediscovery by Welter-Schultes et al (2008) of Garsault's (1764) work. In their treatment of the amphibian and reptile nomina in this work, Dubois & Bour (2010a) explicitly designated nucleospecies for the genera, without taking into account the fact that, in a few cases, Welter-Schultes & Klug (2009) had mentioned a single nominal species as belonging to this genus-while clearly stating that they did not designate nucleospecies in their paper.…”
Section: Modes Of Designation Of Onomatophoresmentioning
confidence: 98%
“…Twenty-two of the 34 bird names in Garsault (1764) are the same as those in Brisson (1760) for the same species concept (disregarding a single-letter difference in the spelling of one name and a hyphen), including ‘Anser domesticus’. The remaining 12 names used by Garsault (1764) show no clear pattern that might imply a single source, as noted by Welter-Schultes & Klug (2009), but none is novel, all of them having been used by pre-Linnean authors, e.g., Gessner (1555, 1560), Aldrovandi (1603 and other volumes), Belon (1555, 1557), Barrère (1745) or Charleton (1668, 1677). Several of Garsault’s (1764) two-word names, e.g., ‘Alcedo muta’ for Common Kingfisher and ‘Aquila regalis’ for Golden Eagle, do not follow Linnaeus’ names (these being Alcedo ispida Linnaeus, 1758 and Aquila chrysaetos Linnaeus, 1758).…”
Section: Authorship and Dating Of The Name Anser Domesticus For Domes...mentioning
confidence: 96%
“…Each is given a French and Latin name on the relevant plate, and these are repeated in the index. Critically, Garsault (1764) deployed only one- or two-name epithets, and thus is a work rooted in binominal nomenclature making his names available (Welter-Schultes et al . 2008, Welter-Schultes & Klug 2009, 2011).…”
Section: Authorship and Dating Of The Name Anser Domesticus For Domes...mentioning
confidence: 99%
See 1 more Smart Citation
“…Judging from other illustrations, the pale lateral band in this illustration is merely the artist's device to indicate the round form. No locality was given, but the neighbourhood of Paris, where Garsault worked (welteR-scHultes et al 2008) is the most reasonable assumption. This would be compatible with occurrences of fr in that area (zeMAnovA et al 2016).…”
Section: Taxonomymentioning
confidence: 99%